Use of botulinum toxin in the management of dystonia in Parkinson’s disease - Anandan, Charenya; Jankovic, Joseph (Frontiers in Neuroscience, 2024)
Botulinum toxin is one of the most potent neurotoxins, but when injected into an overactive muscle, it can transiently alleviate an involuntary movement, such as dystonia. The primary aim of this article is to provide a comprehensive review of the various forms of dystonia observed in patients with Parkinson’s disease who can benefit from a therapeutic trial of botulinum toxin. Although most of these indications are not supported by randomized controlled clinical trials and, therefore, not approved by the Food and Drug Administration, there are many open-label trials supporting a large body of empirical experience testifying to the benefits of botulinum toxin treatment in these conditions.